Pengaruh Pertumbuhan Ekonomi, Inflasi dan Pendidikan terhadap Kemiskinan di Provinsi Jambi Tahun 2002 – 2020 - Putri Maya Mentari (Science of Management and Students Research Journal (SMS), 2021)
Poverty is a condition in which a person or group of people is unable to fulfill their basic rights to maintain and develop a dignified life. This study aims to determine the effect of economic growth, inflation and education on poverty in Jambi province. Based on the results of the SPSS analysis tool that the authors get research results in the form of economic growth variables that have no effect on the poverty level, it can be done by comparing the t count value of 2.106 and t table of 2.109, thus t count < t table, then Ha is rejected and H0 is accepted. Thus, it can be concluded that there is no influence between economic growth on the poverty level of Jambi Province. and it means that the value of economic growth does not have a positive effect but with a significant level (0.050 < 0.05) on poverty in Jambi province. While X2 (Inflation) the inflation variable is significant to the poverty level, it can be done by comparing the t count value of 3,490 and t table of 2,106, thus t arithmetic > t table, then H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant effect of inflation on the poverty level of Jambi Province. and X3 (education) the education variable is significant to the level of poverty, it can be done by comparing the t-count value of 2.109 and t-table of 2.106, thus t-count>t-table, then H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant influence between education on the poverty level of Jambi Province. From the results of the analysis in this study, it can be concluded that inflation has a positive and significant effect on the poverty level of Jambi Province. And Economic Growth does not have a positive but significant effect on the poverty level of Jambi Province. While education has an effect on the poverty level of Jambi Province.